Theory and application of statistical energy analysis - Lyon, Richard H. (Butterworth-Heinemann, 1995)
This up-to-date second edition provides a comprehensive examination of the theory and application of Statistical Energy Analysis (SEA) in acoustics and vibration. Complete with examples and data taken from real problems this unique book also explores.